The Impact of Customer Expectations as a Mediating Variable In the Relationship between Perceived Value, Previous Experience,Perceived Reputation and Brand Loyalty: A Field Study on Commercial Banks in Egypt - Ajban, Rezk (The Arab Journal of Administration, 2023)
This study aimed to determine the effect of Perceived value, Perceived reputation, previous experience on brand loyalty for commercial bank clients in Egypt, while studying the mediating role of customer expectations as a mediating variable in the relationship between Perceived value, Perceived reputation, previous experience and brand loyalty, and the researcher followed the descriptive analysis approach to analysis data, where a questionnaire consisting of (26) questions to collect data. The required data was collected from (384) sample of clients of commercial banks in Egypt, and the data was analyzed using the SPSS program to test the hypotheses of the study., the results of the study showed a positive effect of Perceived value, Perceived reputation, previous experience on brand loyalty., The results of the study also showed that customer expectations mediate the relationship between Perceived value, Perceived reputation, previous experience and brand loyalty. The results of the study indicated that customer expectations are among the main determinants of their consumer experiences, their perception of the value and reputation of the bank, their satisfaction and loyalty to the bank. Therefore, knowing what customers expect in advance is critical to successful marketing strategies for building customer loyalty.